STUDENTS’ DIFFICULTIES IN USING PERSONAL PRONOUNS IN WRITING RECOUNT TEXT - Herman, Herman; Sinaga, Helty; Hutauruk, Bertaria Sohnata (Scientia: Jurnal Hasil Penelitian, 2020)
This study is aimed to investigate the students’ difficulties in using personal pronouns in writing recount text at grade eight of SMP Negeri 8 Pematangsiantar”. In this research, the problem is as follows: “What are the students’ difficulties in using personal pronouns in writing recount text at grade eight of SMP Negeri 8 Pematangsiantar?”. The objective is to find out the students’ difficulties in using personal pronouns at grade eight of SMP Negeri 8 Pematangsintar. To answer the problem above, the researcher intends to use the theories of Collins (2014), Siahaan (2007), Derewinka (1990), William (2005), Frank (1972). The methodology used in this research is the Qualitative research. The subject of this research is grade Eight of SMP Negeri 8 Pematangsiantar. The data collected by observation. After analyzing the data, the researchers found that there were three kinds of students’ difficulties in using personal pronouns in writing text, namely: Personal pronoun as subject (34%), personal pronouns as the object (24%), and personal pronoun as a possessive adjective (42%). It can be concluded that the students at grade eight of SMP Negeri 8 Pematangsiantar still have difficulties in using personal pronouns when they write a recount text based on their experience. The researchers suggest the students’ should memorize the kinds of personal pronouns so they can use it well.